Change in Farming Orientation from Holticulture to Monoculture (A Review of Social Change) - Widodo, Teguh; Susanti, Rina (International Journal of Contemporary Sciences (IJCS), 2024)
The agricultural sector plays a crucial role in meeting societal needs but is undergoing significant transitions. Farmers are increasingly shifting from cultivating food crops, such as rice and vegetables, to industrial crops like oil palm. This shift is driven by economic factors, with farmers perceiving industrial crops as more lucrative due to their higher market value. The transition also reflects broader social changes, as described by Gillin and Gillin's concept of social change, where variations in material culture and ideology influence community lifestyles. Using a qualitative approach, this study explores the socio-economic drivers of this phenomenon and its implications. Findings suggest that dissatisfaction with the economic value of traditional crops and increased awareness of new agricultural opportunities, facilitated by innovation and information access, are key factors. This trend aligns with Etzioni Halevy's linear societal development patterns, highlighting the interplay between economic incentives and social evolution. Understanding these dynamics is essential for managing agricultural transitions to ensure sustainable practices, food security, and socio-economic stability.